Chemical Composition of Essential Oil, Phenolic Compounds Content, and Antioxidant Activity of Cistus monspeliensis from Northern Morocco - Sara Haida; Kaltoum Bakkouche; Abdelaziz Ramadane Kribii; Abderahim Kribii (Biochemistry Research International)
Currently, oxidative stress is one of the major problems that threatens human health. It is at the root of many diseases such as cancer. Despite the enormous efforts provided to combat this scourge, oxidative stress is still relevant and hence comes the need for research of new remedies especially from natural origin. For this purpose, the study of the antioxidant activity of extracts of Cistus monspeliensis from Morocco is a principal research objective. The phenolic extracts were obtained by maceration of the plant in a water/acetone mixture and then separated by liquid/liquid extraction with solvents of increasing polarity. The first phytochemical tests carried out on these extracts showed the existence of different families of phenolic compounds, such as flavonoids, tannins, and others. Assays for total polyphenols, flavonoids, hydrolysable, and condensed tannins were carried out by known colorimetric methods. The results of these assays have shown that the studied extracts are rich in phenolic compounds present in the plant in the form of flavonoids (69.81 ± 0.22 mg EQ/g DM), hydrolysable tannins (61.86 ± 0.89 mg ETA/g DM), and condensed tannins (70.05 ± 1.61 mg EC/g DM). The evaluation of the antioxidant activity is carried out by two different methods: the DPPH test (2,2-DiPhenyl-1-Picryl-Hydrazyl) and the FRAP test (Ferric Reducing Antioxidant Power). The results obtained show that the extracts of Cistus monspeliensis are active and have interesting antioxidant powers. In particular, the water/acetone (WAE) (IC50 = 0.079 mg/mL) and butanolic (BUE) (IC0.5 = 0.099 mg/mL) extracts are the most active with values comparable to that of ascorbic acid. The interesting results obtained in this study clearly show that Cistus monspeliensis originating from Morocco can be considered as a source of natural antioxidants. Therefore, the extracts of this plant deserve to be tested in the medicinal field, against cancer and cardiovascular diseases, and in food field as an additive and preservative.